Mapeamento sistemático sobre o uso de ontologias em informática médica - Mota, Moises Roberto de Araujo (2013)
The number of studies on the use of Ontologies in Medical Informatics has grown through the years. It shows the interest in developing technologies with semantic bases for this new area of science. However, little work has been documented about how the area has developed, thus hampering the creation process of relevant projects in the field of Medical Informatics, since it is not possible to map the main research opportunities, gaps and needs of this area. Therefore, this project aims to map the overall development of this area, specifically on the use of Ontologies in Medical Informatics, in order to highlight and fill the area needs. For this, we used the methodology of systematic research known as Systematic Mapping, which follows a research protocol clearly defined, transparent and rigorous, enabling the study be evaluated and validated by the scientific community interested reproduced. In this way, the current knowledge was gathered in the literature on the Use of Ontologies in Medical Informatics. From automatic and manual searches, it was returned 23788 studies related to this research area. After conducting a rigorous selection, this number dropped to 511 relevant papers, which were performed on the further analysis for the proposed construction of Systematic Mapping. It was detected 07 characteristics of these studies, which allowed the observation of the main trends of growth of the area as a whole. The quality assessment of the selected works provided security to take conclusions of this research, considering that around 95% have strong evidence to support the presented results. Despite these results, we found some gaps in relation to the depth of this search. We concluded that the use of Ontologies in Medical Informatics has grown as expected,considering the reuse of ontologies, integration and interoperability of systems and different ontologies. About the opportunities, we identified in this area a need for methods for evaluation, validation, correctness, completeness and maintenance of new or already established ontologies, and also the development of applications and studies related totelemedicine, public health, education, robotics, evidence-based research, and financial management, focused on Medical Informatics